Mechanically Twisting‐Induced Top‐Down Chirality Transfer for Tunable Full‐Color Circularly Polarized Luminescent Fibers - Xiaoxiao Yu; Linfeng Chen; Qin Liu; Xiaoqing Liu; Zhenduo Qiu; Xinhai Zhang; Meifang Zhu; Yanhua Cheng (Advanced Science)
Abstract Circularly polarized luminescence (CPL) materials with rich optical information are highly attractive for optical display, information storage, and encryption. Although previous investigations have shown that external force fields can induce CPL activity in nonchiral systems, the unique role of macroscopic external forces in inducing CPL has not been demonstrated at the level of molecule or molecular aggregate. Here, a canonical example of CPL generation by mechanical twisting in an achiral system consisting of a polymer matrix with embedded fluorescent molecules is presented. By carefully adjusting the twisting parameters in time and space, in conjunction with circular dichroism (CD), CPL, and 2D wide‐angle X‐ray scattering (2D WAXS) studies, a twisting‐induced top‐down chiral transfer mechanism derived from the molecular‐level asymmetric rearrangement of fluorescent units is elucidated within polymers under external torsional forces. This top‐down chiral transfer provides a simple, scalable, and versatile mechanical twisting strategy for the fabrication of CPL materials, allowing for fabricating full‐color and handedness‐tunable CPL fibers, where the macroscopic twist direction determines the CPL handedness. Moreover, the weavability of CPL fibers greatly extend their applications in anti‐counterfeit encryption, as demonstrated by using embroidery techniques to design multilevel encryption patterns.